Renforcement des poutres FGM par des plaques FRP (Cas d’imperfection de la poutre) - BOURADA, Fouad; AMARA, Khaled; BOURADA, Mohamed (Science des matériaux (Laboratoire LARHYSS), 2016)
This work presents a method for determining the elastic shear and peel stresses in an adhesive joint between a strengthening plate and functionally graded beam (FGB). The beam is assumed to be isotropic with a constant Poisson’s ratio and exponentially-varying elastic modulus through the beam thickness. The effect of physical imperfection was introduced through a coefficient α which tends to reduce the value of Young modulus of beam FG. An analytical solution is proposed on the basic beam theory; several numerical examples are presented and discussed emphasizing the effect of different parameter governing the evolution of the interface stress.  Keywords: Adhesive stress – FGB Beam – Strengthening